Developing marketing capabilities through export commitment and innovativeness - Malva, Madalena (2017)
This research examines how marketing capabilities, technological capabilities, and organizational innovation influence export performance. More specifically, we examine the impact of marketing and technological capabilities on organizational innovation and the influence of organizational innovation on export performance. We investigate the mediating role of organizational innovation in the relationships between these two capabilities (i.e. marketing and technological capabilities) and export performance. Survey data of 471 exporting manufacturing firms based in Portugal was used to test the relationships between the constructs analyzed in this study. The findings demonstrate that marketing and technological capabilities have a significant effect on organizational innovation intensity, which in turn has a positive impact on export performance. Organizational innovation positively mediates the relationships between marketing and technological capabilities and export performance. Furthermore, the results show that marketing capabilities have a stronger impact on organizational innovation and export performance than technological capabilities. Implications for scholars and practitioners are discussed along with suggestions for future research.